INNOVATIVE APPROACHES TO TEACHING RUSSIAN - Khikmatova Dilrabo Pulatovna (Journals Park Publishing, 2023)
The article discusses the basic principles of the system-activity approach. In practice, various types and techniques of work in this technology are offered.
Keywords: Russian language, innovative training, lesson, student, educational process, distance learning, innovative approach.